Penggunaan Agregat Sungai Batu Tiakka’ dalam Campuran AC-BC - Gabriel Pabia Palimbunga; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2020)
This study was intended to determine the characteristics of the use of the Batu Tiakka River aggregate in the AC-BC Mixture. The method in this study is to conduct a series of testing the characteristics of coarse, fine aggregate, and filler then design the composition of the AC-BC mixture and Marshall test to obtain the mixture characteristics and Marshall immersion test to obtain the residual strength index (IKS) using optimum asphalt content. The results showed that the characteristics of the pavement material in the form of Batu Tiakka River Saluputti District meet the General Specifications of Bina Marga 2018 as a pavement lining material. Through the Marshall test obtained the characteristics of a mixture of AC-BC with asphalt content of 5.00%, 5.50%, 6.00%, 6.50%, 7.00%. The Marshall immersion test results of the AC-BC mixture with an optimum asphalt content of 7.00% obtained a Time Strength Index (IKS) of 93.47% that meets the General Specifications of the 2018 Highways which is 90%. Where the results of this study can be concluded that the Batu Batu aggregate Salakutti Sub-district can be used as road pavement material in AC-BC mixture because it meets the 2018 Bina Marga General Specifications.